2007
DOI: 10.1111/j.1524-4725.2007.33218.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of a Novel Ribose?Cross-linked Collagen Dermal Filler: A Histologic and Histomorphometric Study in an Animal Model

Abstract: Ribose-cross-linked collagen is endowed with a higher functional longevity as assessed in an animal model when compared with the most used collagen-based dermal fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Our results are consistent with those of a previous study by Pitaru et al, which investigated the long-term efficacy of Dermicol-P35 27G in rabbit models. 24 This study reported integration of the Dermicol-P35 27G implant into the dorsal der- Volume 125, Number 6 • Properties of Dermicol-P35 mis of rabbit ears after 1 and 12 months. 24 Over time, fibroblasts colonized areas of the implanted material and produced new collagen.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results are consistent with those of a previous study by Pitaru et al, which investigated the long-term efficacy of Dermicol-P35 27G in rabbit models. 24 This study reported integration of the Dermicol-P35 27G implant into the dorsal der- Volume 125, Number 6 • Properties of Dermicol-P35 mis of rabbit ears after 1 and 12 months. 24 Over time, fibroblasts colonized areas of the implanted material and produced new collagen.…”
Section: Discussionmentioning
confidence: 96%
“…24 This study reported integration of the Dermicol-P35 27G implant into the dorsal der- Volume 125, Number 6 • Properties of Dermicol-P35 mis of rabbit ears after 1 and 12 months. 24 Over time, fibroblasts colonized areas of the implanted material and produced new collagen. 24 In addition, the implants displayed new vascularization after 12 months.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The durability of Dermicol-35 27G has been demonstrated in animal models and clinical trials. 18,24 Further, because of the low potential for hypersensitivity, treatment with Dermicol-P35 products does not require a skin test before use. 21 Thus, cosmetic procedures can be performed immediately after consultation.…”
Section: Discussionmentioning
confidence: 99%
“…It is on this basis that proper and reliable preclinical animal-based biocompatibility studies are warranted for each new filler compound (Schuh 2008). Although previously several animal models have been used, including rabbits (Pitaru et al 2007), pigs (Farkas et al 2008;Shumaker et al 2006), rats (Hillel et al 2012), and mice (Ramires et al 2005), there is no specific animal model that is considered a gold standard for assessing safety or efficacy of tissue fillers (Hillel et al 2012). Furthermore, to our knowledge, there is no reliable data source for interspecies differences in reaction to the use of tissue fillers.…”
mentioning
confidence: 99%